2018
DOI: 10.1016/j.aim.2017.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Ramanujan coverings of graphs

Abstract: Let G be a finite connected graph, and let ρ be the spectral radius of its universal cover. For example, if G is k-regular then ρ = 2 √ k − 1. We show that for every r, there is an r-covering (a.k.a. an r-lift) of G where all the new eigenvalues are bounded from above by ρ. It follows that a bipartite Ramanujan graph has a Ramanujan r-covering for every r. This generalizes the r = 2 case due to Marcus, Spielman and Srivastava [MSS15a].Every r-covering of G corresponds to a labeling of the edges of G by element… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…This connection tells us that the lift graph incurs the eigenvalues of the base graph, while its new eigenvalues are the union of eigenvalues of a collection of matrices arising from the irreducible representations of the group and the group elements assigned to the edges. This connection has been recently used in [HPS15] in the context of expansion of lifts, aiming to generalize the results in [MSS15]. In order to understand the expansion properties of the lifts, we focus on the new eigenvalues of the lifted graph.…”
Section: Our Resultsmentioning
confidence: 99%
“…This connection tells us that the lift graph incurs the eigenvalues of the base graph, while its new eigenvalues are the union of eigenvalues of a collection of matrices arising from the irreducible representations of the group and the group elements assigned to the edges. This connection has been recently used in [HPS15] in the context of expansion of lifts, aiming to generalize the results in [MSS15]. In order to understand the expansion properties of the lifts, we focus on the new eigenvalues of the lifted graph.…”
Section: Our Resultsmentioning
confidence: 99%
“…The papers [15][16][17] cite theorems in the original arxiv version of this work [6], which are numbered differently from the ones in this paper. In particular, Theorems 1.7 and 1.8 of [6] correspond to Theorems 1.12 and 1.14 of this paper.…”
Section: Remark 111 (Renumbered Theorems)mentioning
confidence: 99%
“…Proof Note that equality in (17) clearly implies equality in (16). Now, assume by way of contradiction that ( 16) is false, and let x = maxroot ( f ).…”
Section: Transform Boundsmentioning
confidence: 99%
“…However, recently, in [5], Marcus, Spielman, and Srivastava proved that every bipartite Ramanujan graph has a Ramanujan 2-covering graph, which showed that there were an infinite number of Ramanujan graphs of any degree of regularity. In [3], Hall, Puder, and Sawin generalized this result by proving that every bipartite graph without self-loops has a Ramanujan d-covering for every d. To do so, they introduced the d-matching polynomial. Definition 1.1.1.…”
mentioning
confidence: 99%
“…, d}, and G λ is the d-cover corresponding (in a sense which will be made precise in Section 2.3) to a given labeling λ ∈ L d (G). Essentially, the d-matching polynomial is the average of all of the (classical) matching polynomials that come from the d-covers of a graph G. It is known due to Heilmann and Leib in [4] that the matching polynomial has only real roots when G has no self-loops, and Hall et al showed that the d-matching polynomial shares this important property [3]. Independently, Hall made the following conjecture:…”
mentioning
confidence: 99%